Kimbap as a Postcolonial Arena: Culinary Contestation and the Repositioning of Korean Cultural Identity towards Japan - Faris Asyraf Widiantoro; Adi Kristina Wulandari (Dinasti Publisher, 2025)
The Hallyu phenomenon has increased global interest in Korean cuisine, including kimbap. However, the history of kimbap raises debates over its origins, whether it is a Joseon tradition (Bokssam) or an adaptation of Japanese sushi during the colonial period. This article analyzes how kimbap became a symbol of resistance to the repositioning of postcolonial Korean cultural identity. Using a qualitative method with a literature review, this study shows that South Korea's attempt to separate kimbap from sushi is a cultural strategy to assert autonomy and uniqueness. Kimbap functions as a